The Disappearing Subject: Language, transparency, and modern architecture in the works of Michel Houellebecq. - Grass, Delphine (Contemporary French & Francophone Studies, 2011)
The article focuses on the theory of author Michel Houellebecq regarding language, modern architecture frameworks, and transparency of technology in modern communication systems. It mentions that the book of Houellebecq entitled "Extension du domaine de la luute" says that the interactions of human on technology are not facilitated. It states that the modern architecture models that were described in the novels of Houellebecq was organized under the modern communication ethics.